Identification of Pending Claim Factors at X Hospital City of Medan in 2021 - Flora Junita Sirait; Ermi Girsang; Sri Lestari Ramadhani Nasution (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
An overview of Covid 19 claims in the city of Medan submitted for the period March 2020 to November 2021 amounted to IDR 5.046 trillion, of which IDR 4.767 trillion has been verified (94.71%) and IDR 1994 trillion is pending (33,868 cases). This research aims to identify pending claim factors at one of the Covid-19 referral hospitals in Medan City in 2021. The location that will be used in this research is the Murni Teguh Memorial National Health Insurance Billing Unit. Researchers conducted interviews with informants regarding Covid-19 claims and the sample used in this research was purposive sampling, namely a sample that was considered representative of the research data by meeting the criteria, namely inclusion and exclusion. Data analysis was carried out through several stages, namely data reduction, data display and verification. The results of the research are that the factors that cause delays in hospitals are the INACBG application update, communication between patients and the doctor in charge is less open regarding clinical complaints and travel history out of town or abroad, the number of human resources is insufficient compared to patients numbering up to thousands with an HR ratio of 1: 1685 patients and DPJP 1:96 patients, this was also experienced by several other hospitals as stated in the journal entitled Review of Inpatient Claim Dispute Settlement for Corona Virus Disease 2019 (Covid-19) Patients at Ajibarang Regional Hospital in 2020 and officers had problems in implementing Covid-19 claims, namely changes in regulations up to 6 times in 3 years, so that it caused a lot of miscommunication with officers on duty within the scope of Covid-19 services, but this change in regulations was due to adapting to Covid-19 conditions. Keywords: Covid-19, Identification, Pending, Social Security Administrator